Shareholder activism and internationalization in the family firm - Bobillo, Alfredo M.; Rodríguez-Sanz, Juan A.; Tejerina-Gaite, Fernando (Journal of Business Economics and Management, 2013)
We present the internationalization of the family firm (FF) as a corporate growth strategy that is sometimes necessary to ensure survival. The different generations running the family firm (GFF) are likely to be constrained, not only by the demands of the business itself, but also by activism from non-management family shareholders. In this paper, we perform an analysis of a sample of Spanish family firms, both domestic and multinational, for the period 2000–2009. The results of this analysis show evidence of a positive relationship between the scope of internationalization and two other variables: family activism (FAI) and life cycle duration of the family firm (DLFF). When it comes to seeking alternative ways to create economic value and obtain debt finance, each generation is less risk averse than the preceding one. However, increasing family conflict over successive generations instigates economic value-destroying behavior. Overall, our findings suggest that economic value creation, leverage and international diversification in FFs will be conditioned not only by the ownership structure and size of the company, but also by the firm's current point in the business life cycle, the generation that is in charge, and activism from other family members, all of which play a decisive role in the FF internationalization and economic value creation process.